Ultra-rapid Idylla™ EGFR mutation screening followed by next-generation sequencing: An integrated solution to molecular diagnosis of non-small cell lung cancer - Qiu, Tian; Zhang, Fanshuang; Zheng, Bo; Feng, Zitong; Li, Weihua; Zeng, Hua; Chu, Lixia; Ying, Jianming (Frontiers in Oncology, 2023)
Background: Rapid profiling of the EGFR mutations is crucial to help clinicians choose the optimal treatment for patients with advanced/metastatic Non-Small Cell Lung Cancer (NSCLC). Unfortunately, current diagnostic techniques, including ARMS-PCR and NGS, generally require several days to deliver final results. This diagnostic delay may lead to treatment delays for patients who are worsening rapidly. Methods: This study introduced the ultra-rapid IdyllaTM system for rapid, sensitive and specific identification of the EGFR mutations among Chinese NSCLC patients. IdyllaTM EGFR Assay, an integrated cartridge running on the IdyllaTM system, which can detect 51 EGFR mutations directly from Formalin-Fixed, Paraffin-Embedded (FFPE) samples within 2.5 hours, was used in this study. The sensitivity and specificity of the IdyllaTM system were evaluated in comparison with ARMS-PCR or NGS using 95 clinical samples. Results: The IdyllaTM system achieved a sensitivity of 97.6%, a specificity of 100%, and an overall concordance of 97.9% for 95 retrospective samples. When compared to ARMS-PCR, the IdyllaTM system demonstrated high accuracy with an overall agreement of 97.1% (34/35), a sensitivity of 95.2% (20/21) (95% CI, 76.2% - 99.9%), and an estimated specificity of 100% (12/12) (95% CI, 76.8% - 100%) for 35 prospective samples. Conclusions: This Idylla system provides a rapid, accurate and simple approach for screening EGFR mutations, which can guide Tyrosine Kinase Inhibitors (TKI) treatment for NSCLC patients in a timely manner.